Ecclesial identification beyond late modern individualism? : a case study of life strategies in growing late modern churches - Tangen, Karl Inge. (Global Pentecostal and Charismatic Studies, 2012)
Why do some late modern churches grow, counter to the trend in Western Europe? Why do people identify with such churches - and does identification lead to morally transforming commitments beyond late modern consumerism? This case study investigates these questions based on 'real life' or empirical research, which include both the level of individual life strategies and organisational practice in two growing European churches. This innovative and interdisciplinary study draws on recent findings in theology, moral philosophy, sociology and organisational psychology. Its findings may prove useful not only for scholars in these disciplines, it may also enrich the reflection of practitioners who seek to perform the difficult art of transformational leadership in a late modern context.